Usefulness of Once-Weekly GLP-1 Receptor Agonist Semaglutide on Glycemic Control in Subjects with Type 2 Diabetes Mellitus: Switching from the Same Class Dulaglutide in a Retrospective Observation Study - Tomohiko Kimura; Masato Kubo; Kaio Takahashi; Ryo Wamata; Yuichiro Iwamoto; Hideyuki Iwamoto; Yukino Katakura; Junpei Sanada; Yoshiro Fushimi; Masashi Shimoda; Fuminori Tatsumi; Shuhei Nakanishi; et al. (Journal of Diabetes Research, 2024)
Recently, the development of once-weekly incretin-based injections dulaglutide and semaglutide has drawn a great deal of attention. This study is aimed at comparing the efficacy of once-weekly GLP-1 receptor activator (GLP-1RA) dulaglutide and semaglutide on glycemic control and several metabolic parameters in patients with type 2 diabetes mellitus. We compared various clinical parameters between before and after switching from dulaglutide to semaglutide in “study 1” (pre-post comparison) and set the control group using propensity score matching method in “study 2.” In “study 1,” six months after the switching, HbA1c was significantly reduced from 8.2% to 7.6% and body mass index was also decreased from 30.4 kg/m2 to 30.0 kg/m2. Such effects were more pronounced in subjects whose glycemic control was poor. In “study 2,” after 1 : 1 propensity score matching, glycemic control and body weight management were improved in the switching group compared with the dulaglutide continuation group. In this study including obese subjects with poor glycemic control, switching dulaglutide to semaglutide showed more beneficial effects on both glycemic and weight control irrespective of age, body weight, and diabetes duration. Therefore, we should bear in mind that it would be better to start using a relatively new once-weekly GLP-1RA semaglutide in clinical practice, especially in obese subjects with poor glycemic control with other GLP-1RAs.